2021
DOI: 10.3390/ijerph18168272
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Strain Injury (HSI) Prevention in Professional and Semi-Professional Football Teams: A Systematic Review and Meta-Analysis

Abstract: Hamstring Strain Injuries (HSIs) are the most common type of lesion in professional footballers and the leading cause of absence days from sports. However, recent studies have shown that high-level football teams apparently do not apply any HSI prevention protocol. The aim of the study was to determine the effect of preventive strategies and protocols in reducing the incidence of hamstring muscle injuries in professional and semi-professional football teams. A literature search of PubMed/MEDLINE, ISI/Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 68 publications
(98 reference statements)
2
40
0
3
Order By: Relevance
“…Our findings indicate that teams that implemented NHE in team training and used it with most players had fewer hamstring injuries than teams that only used the NHE for individual players with current or a history of a hamstring injury. We acknowledge that the generalisability of our findings outside of the study cohort is uncertain although a previous study on top-tier clubs in Norway showed similar adoption rates as in the ECIS clubs,10 and preventive efficacy of the NHE has mainly been documented in subelite teams 5–8…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our findings indicate that teams that implemented NHE in team training and used it with most players had fewer hamstring injuries than teams that only used the NHE for individual players with current or a history of a hamstring injury. We acknowledge that the generalisability of our findings outside of the study cohort is uncertain although a previous study on top-tier clubs in Norway showed similar adoption rates as in the ECIS clubs,10 and preventive efficacy of the NHE has mainly been documented in subelite teams 5–8…”
Section: Discussionmentioning
confidence: 86%
“…We acknowledge that the generalisability of our findings outside of the study cohort is uncertain although a previous study on top-tier clubs in Norway showed similar adoption rates as in the ECIS clubs, 10 and preventive efficacy of the NHE has mainly been documented in subelite teams. [5][6][7][8] Player availability is a key indicator for team performance, 24 and absence due to hamstring injuries is a big problem for most teams. Our study shows that teams that implemented NHE in team training had a lower injury burden 100 days fewer injury absence days per team and season on average.…”
Section: How Can Our Findings Be Of Practical Value For Players Clini...mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides specific details on implementation of these practices. At the initial onset of a lockdown, standardized neuromuscular training programs such as the Fédération Internationale de Football Association (FIFA 11+), Nordic Hamstring exercise, or Oslo Sports Trauma Research Center (OSTRC) Shoulder Injury Prevention Program should be rapidly implemented to help protect against injury with re-engagement into sport (85,93,94). Continuation of high-intensity training maneuvers will help maintain explosive performance and protect against vulnerable tissues.…”
Section: Mental Health Impact Of Covid On Athletesmentioning
confidence: 99%